SYNTHESIS OF INTELLECTUAL SUBSYSTEMS OF DYNAMIC DIAGNOSIS OF THE CONDITION OF TURBINE UNITS THERMAL POWER - Suleimenov , Alibek; Suleimenov, Batyrbek; Zhirnova, Oxana; Suleimenov , Aituar (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2017)
Technique of creating a sub-line diagnostics status turbine unit thermal power plant based on an analysis of its diagnostic features. Rapid assessment of the technical state of turbine unit allows an early stage to detect the possibility of an emergency and to localize it. It involves the integration of the subsystems of the existing process control system (PCS), which will allow more efficient use of its information, hardware and software. Evaluation of the technical condition of the turbine unit thermal power plant is proposed to determine the use of modern intelligent technologies. The proposed method was used in the development of rapid diagnostic subsystems technical state of turbine of thermal power in Almaty.